NFLUENCE OF HEATING SOURCES USING HYDROGEN-OXYGEN MIXTURE ON STRUCTURE FORMATION DURING SURFACE OF RELETIC MATERIALS - Захаров, Євгеній Анатолійович; Попіль, Юрій Станіславович; Корж, Віктор Миколайович (Problems of Friction and Wear, 2021)
Scanning of power supplies to create a tape relita for surfacing on small parts of warehouse forms, solidification in boxes of energy sources, gas flame, plasma flow in the working gas in the hydrogen-oxygen mixture. Visual skills, formation and formulation of the structure of the welded surfaces in the premises in the thermal characteristics of the concentrated parameters of energy consumption and technological parameters, the presented results of solid matrices, the characteristics of the solid reflection in it.